Active and passive surveillance for bat lyssaviruses in Italy revealed serological evidence for their circulation in three bat species. (4th December 2019) - Leopardi, S.; Priori, P.; Zecchin, B.; Poglayen, G.; Trevisiol, K.; Lelli, D.; Zoppi, S.; Scicluna, M. T.; D'Avino, N.; Schiavon, E.; Bourhy, H.; Serra-Cobo, J.; et al.
Abstract: The wide geographical distribution and genetic diversity of bat-associated lyssaviruses (LYSVs) across Europe suggest that similar viruses may also be harboured in Italian insectivorous bats. Indeed, bats were first included within the passive national surveillance programme for rabies in wildlife in the 1980s, while active surveillance has been performed since 2008. The active surveillance strategies implemented allowed us to detect neutralizing antibodies directed towards European bat 1 lyssavirus in six out of the nine maternity colonies object of the study across the whole country. Seropositive bats were Myotis myotis, M. blythii and Tadarida teniotis. On the contrary, the virus was neither detected through passive nor active surveillance, suggesting that fatal neurological infection is rare also in seropositive colonies. Although the number of tested samples has steadily increased in recent years, submission turned out to be rather sporadic and did not include carcasses from bat species that account for the majority of LYSVs cases in Europe, such as Eptesicus serotinus, M. daubentonii, M. dasycneme and M. nattereri. A closer collaboration with bat handlers is therefore mandatory to improve passive surveillance and decrypt the significance of serological data obtained up to now.